A Comprehensive Review of Fragile X Syndrome and Fragile X Premutation Associated Conditions in Africa - Mbachu, Chioma N. P.; Mbachu, Ikechukwu Innocent; Hagerman, Randi (MDPI, 2024)
This manuscript corresponds to the peer-reviewed article published in Genes (2024), 15(6), 683. https://doi.org/10.3390/genes15060683 . The article is distributed under the Creative Commons Attribution (CC BY 4.0) license. Fragile X syndrome (FXS) is a genetic disorder caused by a mutation in the fragile X messenger ribonucleoprotein 1 (FMR1) gene and known to be a leading cause of inherited intellectual disability globally. It results in a range of intellectual, developmental, and behavioral problems. Fragile X premutation-associated conditions (FXPAC), caused by a smaller CGG expansion (55 to 200 CGG repeats) in the FMR1 gene, are linked to other conditions that increase morbidity and mortality for affected persons. Limited research has been conducted on the burden, characteristics, diagnosis, and management of these conditions in Africa. This comprehensive review provides an overview of the current literature on FXS and FXPAC in Africa. The issues addressed include epidemiology, clinical features, discrimination against affected persons, limited awareness and research, and poor access to resources, including genetic services and treatment programs. This paper provides an in-depth analysis of the existing worldwide data for the diagnosis and treatment of fragile X disorders. This review will improve the understanding of FXS and FXPAC in Africa by incorporating existing knowledge, identifying research gaps, and potential topics for future research to enhance the well-being of individuals and families affected by FXS and FXPAC.
This manuscript corresponds to the peer-reviewed article published in Genes (2024), 15(6), 683. https://doi.org/10.3390/genes15060683 . The article is distributed under the Creative Commons Attribution (CC BY 4.0) license. The present upload is an author-archived version provided for open dissemination via AfricArXiv.
Keywords: Africa; Fragile X syndrome; FMR1 premutation; FXTAS; FXPOI; Fragile X Premutation